How are small and medium enterprises in Malaysia’s furniture industry coping with COVID-19 pandemic? early evidences from a survey and recommendations for policymakers - Ratnasingam, Jegatheswaran; Khoo, Albert; Jegathesan, Natkuncaran; Lum, Chee Wei; Abd Latib, Hazirah; Thanasegaran, Ganesh; Lim, Choon Liat; Lee, Yan Yi; Othman, Kamaruzaman; Amir, Mohd Afthar (North Carolina State University, College of Natural Resources, 2020)
In the wake of the global COVID-19 pandemic and the subsequent movement control order (MCO) in Malaysia, an on-line survey was undertaken involving 748 small and medium enterprises (SMEs) in the furniture industry. The main objective was to examine the impact of the pandemic and the subsequent MCO on the various business aspects of the SMEs as well as to make recommendations to the government on supportive measures for the SMEs. The survey found that although all aspects of the business were impacted, the two major concerns of the SMEs during this crisis were the financial management and the supply chain disruptions. Inevitably, it was found that most of the SMEs were operating well below capacity, which was a huge financial strain on their business viability. It was recommended that the government provide measures to help the SMEs manage their cash-flow and ease the restrictions to facilitate supply-chain commencement that is crucial to their business. The survey also revealed that most SMEs acknowledged the importance of automation and the adoption of technologies. Respondents regarded the shift towards Industry 4.0 was inevitable as a means increase their resilience when facing future uncertainties.